More than meets the eye - Johansen, Iris; Johansen, Roy (New York : Grand Central Publishing, 2023)
"Serial killer James Michael Barrett leads a grim parade of police officers, FBI agents, and forensics into the woods of Pine Valley, forty-five miles east of San Diego. At the end of the second week of his high-profile murder trial, he has struck a plea deal with the prosecution: he'll reveal the location of his last victim's body in exchange for the D.A. taking the death penalty off the table." --
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Women private investigators -- Fiction; Murder -- Investigation -- Fiction; Serial murderers -- Fiction; San Diego (Calif.) -- Fiction; Detective and mystery fiction; Thrillers (Fiction)